Cystic duct dysplasia after cholecystectomy: a systematic review of the literature - Mongelli, Francesco; Cianfarani, Agnese; Di Giuseppe, Matteo; Ferrario Di Tor Vajana, Antonjacopo; Saporito, Andrea; Garofalo, Fabio; La Regina, Davide (International Surgery Journal, 2019)
Approximately 1 to 3.5% of cholecystectomies are found to have incidental dysplasia on histological examination. Cases of positive resection margins on the cystic stump are rare and evidence lack. The aim of this article was to systematically review the literature and to suggest a possible management algorithm. We searched PubMed, Cochrane Library and Google Scholar databases by combining “cholecystectomy” and “dysplasia” and “cystic” according to preferred reporting items for systematic reviews and meta-analyses guidelines. Studies providing information about cystic duct dysplasia with positive resection margin after cholecystectomy were included. We identified 113 articles, of which three were considered eligible. Five patients had a high-grade dysplasia, one patient had a carcinoma and one had a low-grade dysplasia. Median follow-up was of 10.5 months (range: 0.5-26.6 months), no evidence of recurrence was found in patients with dysplasia, while the patient with diagnosis of cholangiocarcinoma died during follow-up. Patients with positive resection margins for dysplasia after cholecystectomy should be considered for a surgical treatment according to clinical and pathological factors. Simple cystic duct stump excision was suggested and seems to be safe and effective with no evidence of recurrence during follow-up when a R0 resection is achieved. A multidisciplinary approach and a surveillance program should be always taken into account.